Effects of pressure on the survival and viability of cancer cells in vitro: An analytical study - Mohsin Ali Khan; Zaw Ali Khan; Ishrat Husain; Shivbrat Upadhyay; Sarina Zehra; Rumana Ahmad (PLoS ONE, 2025)
Intense cancer research is underway to discover possible therapies but no major breakthrough appears to be in sight in terms of its cure when diagnosed late. The cytostatic and growth inhibitory effect of high pressure on cells is well documented. In the present study, two cancer cell lines viz. MDA-MB-231 (breast carcinoma) and A549 (lung carcinoma) and one normal cell line (Vero) were subjected to increased pressure of 18 psi in a specially constructed pressure chamber. It was found that a pressure of 18 psi induced a significant change in the growth parameters of both cancer cell lines versus normal cells. Exposure to increased pressure greatly increased the proportion of MDA-MB-231 cells in the S phase while concurrently reducing the number of cells in the G0/G1 phase as compared to their untreated counterparts. SEM and AFM analysis revealed presence of characteristic ‘pores’ and ‘pits’ on the cell surface of pressure-treated versus untreated cancer cells. TEM analysis also revealed significant intracellular differences between pressure-treated and untreated cancer cells. Hyperbaric nitrogen therapy is proposed as a novel cancer-treatment modality involving administration of N2 at the tumor site in murine models of breast and lung cancer. This would eventually pave the way for development of a device effective treatment strategy for human tumors in future.